Exploring the relation between socioeconomic position and DNA methylation in a European population. (30th September 2020) - Petrovic, D; Carmeli, C; Bodinier, B; Chadeau-Hyam, M; Ehret, G; Dhayat, N; Ponte, B; Pruijm, M; Bochud, M; Stringhini, S
Abstract: Background: Previous investigations have reported that adverse socioeconomic circumstances across the life-course lead to the alteration of major biological processes, eventually resulting in a higher disease risk and premature death. In particular, a low life-course socioeconomic position (SEP) has been associated with a modified epigenetic signature of loci involved in inflammation, the physiological response to stress, and other regulatory processes. Methods: In this study, we investigated the association between nine indicators of SEP across the life-course and the differential methylation of 451'000 genome-wide CpG markers, using data from 690 adults included in a Swiss population-based study. We further examined the interrelations between the SEP-related CpGs, and the biological pathways in which the identified markers are involved. Results: Three SEP indicators in adulthood were associated the differential methylation of 161 genome-wide CpG markers, whereby 156 CpGs were less methylated in people with low versus high SEP. Among the identified CpGs, a substantial proportion of markers were no longer associated with SEP upon accounting for health behaviors and cardiometabolic disorders. In addition, the identified CpGs were found to be involved in immune, inflammatory, and cancer-related processes. Conclusions: Our results support the hypothesis that adverse socioeconomic circumstances may lead to the dysregulation of inflammatory processes, eventually resulting in the occurrence of serious chronic conditions such as atherosclerosis, diabetes, or cancer. Key messages: Socioeconomic position is a major determinant of health-related outcomes. Epigenetic modifications may constitute a biological mechanism through which socioeconomic circumstances affect health.